Seminar Meningkatkan Cara Berfikir Kreatif dan Inovatif Generasi Muda Gereja HKBP Simalingkar B Resort Kwala Bekala, Medan - Anne Malau; Herti Diana Hutapea; Imelda Sitinjak; Rimbun C.D. Sidabutar (LPPM Universitas HKBP Nommensen, 2023)
The purpose of this community service activity is to assist the Church's Young Generation in preparing everything to face competition in the future by thinking creatively and innovatively with a Christian perspective. One of the vocations of the Church is to improve welfare and solve youth delinquency problems by helping youth change their mindset to be creative and innovative with the support of one of the Tri Dharma of higher education, namely community service, which greatly assists the church's vocation to care for today's youth. The younger generation needs to be equipped with an understanding related to changing mindsets and increasing creative and innovative mindsets. This seminar is a motivational lecture to understand how to make changes and creativity for a productive and quality life from a Christian view. This seminar was held on Sunday, 15 May 2022, at the HKBP Simalingkar B Resort Kwala Bekala Church, Jalan Pintu air IV gg. HKBP Kwala Bekala, Medan Johor District, which was attended by 47 students (HKBP Simalingkar B Resort Kwala Bekala, accompanied by Resort Priests, Young Priests, Bibelvrow, and Church elders. The implementation began with the Opening of the Resort Priest by singing and praying together, then continued by the MC, and then filled in by the first resource person by providing material, question and answer session, ice breaking, then filled again by the second resource person by providing material, question and answer session, ice breaking, feedback from participants, then closed with a short service of singing and praying and taking photos together.